EFFECTS OF 8-WEEKS SYSTEMATIC CORRECTIVE EXERCISE PROGRAM ON BODY POSTURE AND STABILITY IN PRONATION DISTORTION SYNDROME - Ghazal Hussain; Saima Riaz; Hafsa Khan; Aleena Waheed; Sidra Ghias (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: A postural entanglement in the lower extremitythat initiates with feet contorting to hyper-pronation, leading to other dysfunctional patterns, is known as pronation distortion syndrome. Exaggerated movement of feet causes forced progression of internal tibial rotation and knee adduction while disturbing body kinetics and gait mechanics.Objective: The purpose of this study was to determine the effects of an 8-Weeks Systematic Corrective Exercise program on Body Posture and stability in Pronation Distortion SyndromeMethodology: The study was a randomized controlled trial. It was administered at Riphah International University and Ibrahim Medical Centre Lahore. A convenience sampling technique was utilized to collect the data. A total of 38 subjects were enrolled in the study. All 38 participants were equally divided into two groups. Group A was treated with a conventional and systematic corrective exercise program. Group B underwent conventional treatment consisting of Non-biomechanical functional exercises only. All the participants underwent three sessions per week for 8 weeks.Results: After eight weeks of intervention, the experimental group exhibited significant improvement regarding the Functional movement screening test, navicular drop and valgus ankle angle with p-value